2018
DOI: 10.1016/j.ultsonch.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted extraction of antimicrobial compounds from Thymus daenensis and Silybum marianum: Antimicrobial activity with and without the presence of natural silver nanoparticles

Abstract: The present study is devoted to prepare a new antibacterial and antifungal agent based on in situ-synthesized silver nanoparticles at room temperature using Rosmarinus officinalis (R. officinalis) leaf extract. The Ag-NPs characterization by UV-visible, SEM, TEM and XRD revealed that the particles sizes were in the range of 10-33 nm. In this study, hydroalcoholic extracts were used with ultrasonic method. Ultrasonication has recently received attention as a novel bioprocessing tool for process intensification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…Fernández, et al [ 63 ] found significant inhibition against Fusarium graminearum Schwabe for four flower defensins from milk thistle. Safarpoor, et al [ 64 ] reported moderate antifungal activities of ethanolic extracts of milk thistle against C. albicans and Aspergillus oryzae (Ahlb.) Cohn.…”
Section: Discussionmentioning
confidence: 99%
“…Fernández, et al [ 63 ] found significant inhibition against Fusarium graminearum Schwabe for four flower defensins from milk thistle. Safarpoor, et al [ 64 ] reported moderate antifungal activities of ethanolic extracts of milk thistle against C. albicans and Aspergillus oryzae (Ahlb.) Cohn.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they can be prepared through green synthesis procedures with the aid of plant extracts [ 6 ], which act as reducing and stabilizing agents. Polyol components, polysaccharides, and water-soluble heterocycles (such as those from Stevia rebaudiana [ 7 ], Curcuma longa [ 8 ], Pongamia pinnata [ 9 ], Gliricidia sepium [ 10 ], Eucalyptus hybrida [ 11 ], or Quercus brantii [ 12 ]) have been reported to lead to a synergistic effect in the resulting phytonanocomposites [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology has shown tremendous potential to change society with its varied applications . Nanoparticles (NPs) of zinc, iron, gold, copper and silver are applied in various fields such as pharmaceuticals, agriculture, diagnostics, automotive industry, packaging, paints, etc .…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs) of zinc, iron, gold, copper and silver are applied in various fields such as pharmaceuticals, agriculture, diagnostics, automotive industry, packaging, paints, etc . Their varied applications are due to their medicinal properties, and they can be synthesized using physical, chemical and biological methods . Researchers are interested in synthesizing nanoparticles and studying their size because of their unique physicochemical characteristics and applications.…”
Section: Introductionmentioning
confidence: 99%